TREATMENT OF INGUINALIS LYMPHOSARCOMA IN MALE MINIPOM DOGS - Kristyari, Ni Putu Gita; Pemayun, I Gusti Agung Gde Putra; Wirata, I Wayan (Buletin Veteriner Udayana, 2023)
Lymphosarcoma is a malignant tumor that occurs in the lymphosarcoma system, the cause of lymphosarcoma is not fully known, but there are several risk factors that can trigger the occurrence of lymphosarcoma such as age, genetic changes, infections, chemical radiation, and certain immunodeficiency diseases. This case report aims to find out how to diagnose and treat cases of inguinal lymphosarcoma in dogs. A 2 year old male minipom dog with a weight of 5.6 kg was examined with complaints of a lump in the inguinal area on the dextra penis since 3 weeks. Based on the anamnesis, results of physical examination, observed clinical signs and histopathological investigations, the dog was diagnosed with lymphosarcoma. Animals are then treated with rehabilitation to remove the tumor. Premedication was given subcutaneous atropine sulfate 0.03 mg/kg BB, followed by administration of a combination of xylazine 2 mg/kg BB and ketamine 12 mg/kg BB intravenous. Surgical removal of the tumor is carried out by excision of the tumor mass by separating the nearby tissue. Postoperatively the dog was given cefotaxime injection of 20 mg/kg BB intravenous for 3 days, followed by oral administration of cefixime 5 mg/kg BB for 5 days. Giving anti-inflammatory tolfedine at a dose of 4 mg/kg BB intramuscular for 3 days. On the first day to the seventh day of the surgical wound, enbatic powder was given and the next day, gentamicin sulfate ointment was given. After the operation, the animals were observed to determine the healing of the postoperative wounds, on the 12 day the wounds had dried and fused, and the three stitches had fallen off on their own. Treatment of lymphosarcoma cases is carried out by removing the tumor mass. Healing of the surgical wound was observed on the 12 day. To get maximum results, consider chemotherapy and or radiotherapy to destroy cells that have metastasized in tissues.